Phenotypic characteristic of Staphylococcus aureus from subclinical mastitis in Etawah-crossbreed goats in Yogyakarta, Indonesia - Suwito, Widodo; Nugroho, Widagdo Sri; Adji, Rahmat Setya; Andriani, Andriani; Kusumaningtyas, Eny; Martini, Tri (Veterinary World, 2022)
Background and Aim: Subclinical mastitis (SCM) in Etawah-grade (PE) goats in Yogyakarta, Indonesia, is commonly due to Staphylococcus aureus. At present, S. aureus from SCM in PE goats in Yogyakarta has not been characterized. Therefore, this study aimed to phenotypically characterize S. aureus, which has been isolated from SCM of PE goats. Materials and Methods: A total of 314 lactating PE goats were collected from 60 PE goat farms (e.g., Sleman, Bantul, and Kulonprogo) located in parts of Yogyakarta with an average age of 3-4 years old, three of which showed SCM based on the California mastitis test (CMT). Subclinical mastitis is confirmed in PE goats if CMT shows ++ or +++. Furthermore, S. aureus was detected by biochemical assays. Staphylococcus aureus could determine hemolysin (Hae), coagulase (Coa), clumping factor (Cf), and antibiotic susceptibility. Hemolytic bacteria were detected by culturing on blood agar plate, and Cf was detected by slide agglutination. The production of Coa was detected by tube coagulation. Staphylococcus aureus susceptibility was determined by antimicrobial agar diffusion using a paper disc. Results: Phenotypically characterized S. aureus from PE goats with SCM in Yogyakarta, Indonesia, Coa-, Cf-, and Hae- were found to be resistant to erythromycin (ERYTHRO), ampicillin (AMP), penicillin (PEN-G), and sulfamethoxazole (SULFA). Conclusion: The phenotypic characteristic of S. aureus, which was obtained from SCM in PE goats in Yogyakarta, consists of Coa, and Cf-. S. aureus cannot perform hemolysis of red blood cells. This phenotypic characteristic can prevent and control SCM in PE goats. Several antibiotics such as ERYTHRO, AMP, PEN-G, and SULFA were no longer effective for treating SCM in PE goats because S. aureus has developed its resistance to these antibiotics. Copyright: © Suwito, et al. Open Access.